2000
DOI: 10.4269/ajtmh.2000.63.264
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and tolerability of triclabendazole in Cuban patients with latent and chronic Fasciola hepatica infection.

Abstract: Abstract. Current chemotherapy for the treatment of infections caused by the liver fluke Fasciola hepatica is not satisfactory. Therefore, the efficacy and tolerability of triclabendazole (TCZ) was assessed for this indication. Eightytwo patients (51 female, 31 male, age 15-81 yr, mean 42 yr) with chronic or latent F. hepatica infection refractory to previous anti-helminthic chemotherapy were enrolled in a 60-day open, non-comparative trial. Patients received 20 mg/kg TCZ as two doses of 10 mg/kg administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 19 publications
1
38
0
3
Order By: Relevance
“…Despite medical treatment, 3 (7.6%) patients had to undergo a further invasive procedure. Studies on the efficacy of triclabendazole in fascioliasis revealed a success rate of 79.2% for one dose of 10 mg/kg/day, and a success rate of 92.2% for 10 mg/kg/day over two consecutive days [15,16]. We achieved a 92.4% success rate with the two-dose treatment.…”
Section: Discussionmentioning
confidence: 52%
“…Despite medical treatment, 3 (7.6%) patients had to undergo a further invasive procedure. Studies on the efficacy of triclabendazole in fascioliasis revealed a success rate of 79.2% for one dose of 10 mg/kg/day, and a success rate of 92.2% for 10 mg/kg/day over two consecutive days [15,16]. We achieved a 92.4% success rate with the two-dose treatment.…”
Section: Discussionmentioning
confidence: 52%
“…Since all serum samples were properly preserved at Ϫ70°C from their collection until use, it is possible to speculate that the sensitivities of the two assays were influenced by factors such as the intensity of infection, the persistence of antibodies postinfection, and parasite senescence (21). Northern Peru and Bolivian Altiplano are two regions in which human fascioliasis is highly endemic (3,6,(43)(44)(45)(46). Therefore, it is also possible that the size of the dose of infectious metacercariae could affect the development of a detectable antibody response to a particular antigen (47), as human subjects exposed to F. hepatica infections are likely to ingest low doses of metacercariae over long periods.…”
Section: Discussionmentioning
confidence: 99%
“…Double-dose therapy (10mg/kg dose given, and repeated at 12-24 hours) is recommended in heavy infections, or if there is no response to single-dose therapy (116) . Cure rates of 92·2-100% are described in adults with a two-dose regimen (117,118) , with 79·2% cure rates described with the single-dose regimen (119) . Cure rates of 95% using the 10mg/kg dose have recently been described in children, with 100% cure rates using two doses of 7.5mg/kg (120) .…”
Section: For Clonorchis Sinensis Opisthorchis Viverrini and Opisthormentioning
confidence: 99%